Respostas
respondido por:
1
Tratando-se de um triângulo retângulo, podemos usar a formula de Pitágoras:
(hipotenusa)² = (cateto a)² + (cateto b)²
Hipotenusa = 10
cateto a = 6
cateto b = lado AB
Teremos então:
10² = 6² + (AB)²
100 = 36 + (AB)²
100 - 36 = (AB)²
64 = (AB)²
AB = √64
AB = 8
>> Resposta: 8 cm, Letra D.
(hipotenusa)² = (cateto a)² + (cateto b)²
Hipotenusa = 10
cateto a = 6
cateto b = lado AB
Teremos então:
10² = 6² + (AB)²
100 = 36 + (AB)²
100 - 36 = (AB)²
64 = (AB)²
AB = √64
AB = 8
>> Resposta: 8 cm, Letra D.
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás